2021
DOI: 10.1007/s40120-021-00230-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Knowledge of Alzheimer’s Disease: An Analysis of the Psychometric Properties of the Alzheimer’s Disease Knowledge Scale

Abstract: Introduction: The Alzheimer's Disease Knowledge Scale (ADKS) is one of the most popular instruments for assessing a person's knowledge regarding Alzheimer's disease (AD). The objective of this study was to explore ADKS item characteristics with item response theory (IRT) procedures. Methods: A noninterventional web-based study was conducted. A nonparametric IRT procedure, Mokken analysis, was used to explore the underlying latent structure of the ADKS and ADKS item characteristics regarding scalability and vio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The Dementia Knowledge Assessment Scale (DKAS) is instead a 25 items questionnaire designed to measure knowledge of dementia from a biopsychosocial perspective [ 7 9 ], thus investigating the neurodegenerative condition and its management considering its effects on body, psychological implications, and social interactions [ 8 ]. Compared to other scales (e.g., Alzheimer's Disease Knowledge Scale, ADKS [ 10 ]), the DKAS has better psychometric properties [ 11 ]. Another strength of the DKAS is that it produces, in addition to an overall score for dementia knowledge, four sub-scores on the syndrome causes and characteristics, related risk and protective factors, care consideration and communication with people with the condition [ 7 , 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Dementia Knowledge Assessment Scale (DKAS) is instead a 25 items questionnaire designed to measure knowledge of dementia from a biopsychosocial perspective [ 7 9 ], thus investigating the neurodegenerative condition and its management considering its effects on body, psychological implications, and social interactions [ 8 ]. Compared to other scales (e.g., Alzheimer's Disease Knowledge Scale, ADKS [ 10 ]), the DKAS has better psychometric properties [ 11 ]. Another strength of the DKAS is that it produces, in addition to an overall score for dementia knowledge, four sub-scores on the syndrome causes and characteristics, related risk and protective factors, care consideration and communication with people with the condition [ 7 , 8 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Carpenter et al [ 26 ] analyzed the psychometric attributes of the scale and found that it demonstrates adequate reliability and validity in terms of content and predictive, concurrent, and convergent measures. Because of its high reliability and validity, as demonstrated by other studies [ 11 , 22 , 27 , 28 ] the ADKS was chosen for this study to evaluate nursing students’ knowledge regarding AD.…”
Section: Methodsmentioning
confidence: 99%
“… Alzheimer's Disease Knowledge Scale (ADKS): The scale consists of 30 true/false questions that cover seven areas of knowledge regarding A.D.; these are: assessment (4 questions), symptoms (4 questions), risk factors (6 questions), impact on life (4 questions), care, management (4 questions), and treatment (4 questions) (Table 2 ). The scale has a score ranging from 0 to 30, and it is suitable to use with students and healthcare workers and takes usually 5-10 minutes to complete [ 27 ]. In the current study, the survey was distributed online and the mean time to complete it was 10 minutes calculated based on the electronical measurements.…”
Section: Methodsmentioning
confidence: 99%